2018
DOI: 10.1039/c7sm02540h
|View full text |Cite
|
Sign up to set email alerts
|

Drop spreading and gelation of thermoresponsive polymers

Abstract: Spreading and solidification of liquid droplets are elementary processes of relevance for additive manufacturing. Here we investigate the effect of heat transfer on spreading of a thermoresponsive solution (Pluronic F127) that undergoes a sol-gel transition above a critical temperature Tm. By controlling the concentration of Pluronic F127 we systematically vary Tm, while also imposing a broad range of temperatures of the solid and the liquid. We subsequently monitor the spreading dynamics over several orders o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…As can be seen, at the sol-gel transition the standard deviations are high, however, the determined values of T gel are accurate since their standard deviations are small (Figure 1b). Similar gelation temperatures were already determined [35,36].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As can be seen, at the sol-gel transition the standard deviations are high, however, the determined values of T gel are accurate since their standard deviations are small (Figure 1b). Similar gelation temperatures were already determined [35,36].…”
Section: Resultssupporting
confidence: 80%
“…The gelation temperature decreases linearly with copolymer concentration as shown in Figure 2. This is a common finding, for either Pluronic F127 [35,36] or for other Pluronics [34,37].…”
Section: Resultsmentioning
confidence: 76%
“…This leads to a critical temperature near the contact line below which the liquid locally freezes, leading to the arrest of the spreading, in agreement with experiments. This feature was also reproduced with thermoresponsive polymer solutions [23] on hot substrates. Let us note that the experiments did not exhibit stick-slip dynamics, as the liquid was not continuously forced to spread on the substrate [15].…”
Section: Introductionsupporting
confidence: 54%
“…The temperature difference between the extruded melt and the heated platform, which is very large in 3D printers, is also expected to affect the wetting behavior, as opposed to slot die coating. The effect of the surface temperature on the dynamic contact angle is studied in sessile drop spreading experiments with a thermoresponsive polymer in Reference [35] and alkanes in Reference [36]. In both cases, it is found that an earlier contact line arrest (due to solidification in Reference [36] or to gelation in Reference [35]) leads to larger contact angles compared to isothermal configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the surface temperature on the dynamic contact angle is studied in sessile drop spreading experiments with a thermoresponsive polymer in Reference [35] and alkanes in Reference [36]. In both cases, it is found that an earlier contact line arrest (due to solidification in Reference [36] or to gelation in Reference [35]) leads to larger contact angles compared to isothermal configurations. The study by Pan [37] is the only one led in conditions close to the actual ones in 3D printers: a polyethylene strand is deposited on aluminium and Polyethylene Terephthalate (PET) substrates at different temperatures.…”
Section: Introductionmentioning
confidence: 99%